Performance Determination of New Universal Dryer Models - A. S. Klyuchnikov (Сельскохозяйственные машины и технологии, 2018)
Drying of seed material plays an important part in the system of post-harvest processing and greatly affects the yield quality of the seed material. (Research purpose) Determination of the performance of two modules of a new dryer, taking into account the statistical characteristics of humidity, impurity content and the intensity of submitting the grain heap of various crops to post-harvest processing. (Materials and methods) The research group has tested a mini-module of a new universal dryer developed in the laboratory workshops of Yaroslavl State Agricultural Academy, in the Bolshoye Selo district of the Yaroslavl region. The calculation has been based on the data of the average regional farm. (Results and discussion) It has been determined that the average statistical percentage of moisture removal from the original grain heap was 10.52 percent; gross grain harvest per year – 1,500 tons; the estimated capacity by the dried seed material of the base module is 5 tons per hour, that of the mini module - 0.35 tons per hour. Due to the contribution of Yaroslavl State Agricultural Academy, fully mechanized receiving chambers with air chutes accommodating 300 or 600 cubic meters of heap coming from combines have been introduced into the production lines of post-harvest processing of the crop material. The efficiency calculation of the mini-module has been caused by the need to use it on the farms for the independent supply of high-quality seed material. (Conclusions) The experiment results have confirmed the validity of the calculations and the effectiveness of the new method of drying. In unfavorable weather, grain crops were harvested by a forage harvester and then dried in a mini-module. After processing, high-quality seeds were obtained, the germination rate of which accounted 98-99 percent.